Czech Studies across the Iron Curtain: Dmitry Chyzhevsky’s Collaboration with Czechoslovak Scholars, Based on Their Correspondence, 1956–1977 - Škarpová, Marie (Wiener Slawistischer Almanach, 2024)
The aim of the article is to highlight Dmitry Chyzhevsky’s collaboration (during his “Heidelberg period” 1956–1977) with his colleagues on the other side of a politically divided Europe, namely in Czechoslovakia. Although Chyzhevsky was not able to meet in person with his colleagues in Czechoslovakia on a regular basis, the surviving correspondence between Chyzhevsky and Czechoslovak scholars documents the intensity of their collaboration despite all the political restrictions of the time. The letters provide unique information about the contemporary situation of Slavic and Czech studies on both sides of the Iron Curtain, including the limits faced by scholars at the time. Such correspondence managed to create an unofficial – “parallel” – distribution network for literature on Czech and Slavic studies across the Iron Curtain, one that worked in both directions and made it possible for scholars to obtain literature otherwise unavailable. Secondly, in some cases, the collaborations of Czechoslovak scholars with Chyzhevsky even evolved from commonplace scholarly discussions in the creation of specific cross-border editorial and publishing teams. This is an unrecognized part of both the parallel (humanities) discourse in Czechoslovakia independent or semi-dependent on the official research institutions and independent of publishing activities organized abroad by Czechs.